Choroid plexus carcinoma in adults: an extremely rare case - Ozdogan, Selcuk (Pan Afr Med J, 2015)
Choroid plexus tumors are rare intraventricular papillary neoplasms derived from choroid plexus epithelium, which account for approximately 2% to 4% of intracranial tumors in children and 0.5% in adults. Almost all choroid plexus carcinomas are seen in children and are extremely rare in adults. Headache, diplopia, and ataxia are the most common symptoms usually caused by mechanical obstruction of cerebrospinal fluid flow followed by hydrocephalus, regardless of tumor location. We present an illustrative case with 73 years old male patient who was consulted with headache to our neurosurgery department. In cranial computed tomography, there was a mass in 4(th) ventricle and we confirmed the mass with magnetic resonance imaging. After surgery had been performed, pathology specimen was diagnosed as choroid plexus carcinoma which was rarely seen in this age group.